(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the current status of solid medical waste management at Bau Bang District Medical Center, Binh Duong Province in 2023 Method: Descriptive cross-sectional, mixed quantitative and qualitative research design on 200 observation samples of medical solid waste classification and 20 samples of equipment, preservation, and storage of medical solid waste over time from March 2023 to November 2023 at clinical departments. Results: Solid medical waste was classified at source at 97.5%. Correctly classified medical solid waste includes: 100% minor surgical waste; sharp infectious waste 98.5%, non-sharp infectious waste 87.0%, highly infectious waste 98.0%, non-infectious hazardous waste 94.0%, waste nonrecyclable conventional solid recycled 79.5%. Solid medical waste groups are not collected together, reaching 75.0%. Transporting and storing medical solid waste meets the criteria of 95.0% - 100%. Handover of medical solid waste is fully implemented, and the criteria are 100%. Conclusion: Solid medical waste management at Bau Bang district medical center, Binh Duong province is performed relatively well, there are still some difficulties in implementing medical solid waste management regarding solid waste medical gathering, as well as management facilities.